Urgensi Penyelesaian Kasus Pidana dengan Hukum Adat - Ali Abubakar (Jurnal Madania)
Among the major changes in the orientation of the criminal law is a shift in the concept of fairness of justice on the basis of retaliation towards justice that is restorative justice. Protection and restoration of the rights of victims and the wider community is seen as important as punishment and or rehabilitation of offenders. The process of settlement is not intended solely to punish or embarrass someone, but rather an attempt to obtain a useful truth to help restore a harmonious relationship between the offender, victim, and the community. This is actually not new in the Indonesian archipelago because it familiar in their customary laws and recent legislation passed in the authority. This article explores how the existence of a criminal case settlement with the customary law in terms of sociological, philosophical, and juridical